Handbook of research on Web log analysis - Jansen, Bernard J.; Spink, Amanda; Taksai, Isak, 1948-; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
"This book reflects on the multifaceted themes of Web use and presents various approaches to log analysis"--Provided by publisher.
Section 5. Contextual and Specialized Analysis -- 21. Using Action-Object Pairs as a Conceptual Framework for Transaction Log Analysis -- 22. Analysis and Evaluation of the Connector Website -- 23. Information Extraction from Blogs -- 24. Nethnography: A Naturalistic Approach Towards Online Interaction -- 25. Web Log Analysis: Diversity of Research Methodologies -- Glossary -- Compilation of References -- About the Contributors -- Index.
Includes bibliographical references (p. 538-592) and index.
Also available in print.
Mode of access: World Wide Web.
Keywords: World Wide Web -- Handbooks, manuals, etc; Web usage mining -- Handbooks, manuals, etc; Adaptive dialogue-driven search; Connector Web site; Dynamic Web pages customization; Interaction design; Machine learning approach; Query log analysis; Search log analysis; Search query classification; Search query logs; Transaction log analysis; Very-scale conversation; Web analytics; Web information seeking behavior; Web log analysis; Web log privacy; Web logging data; Web sites; Web usage studies; Web-traffic measurement; Electronic books